Money Management and Tracking Application - Ngoh, Guan Ji; Darman, Rozanawati (Applied Information Technology And Computer Science, 2022)
MyMoney is an application developed to allow the public to manage money and track income or expenses easily. MyMoney is developed to help the public manage money without financial literacy and track daily income or expenses with simple steps. In this application, users can record income and expenses, create a shopping list, add a planned payment, design a retirement financial plan and do analysis for monthly income and expenses. The project is developed based on an iterative development methodology. Implementation of the application will be done by using Android Studio software and Firebase as the database. After implementation, there are a testing phase will be done for collecting feedback and do improvement in the next version to ensure the latest version of the application can be satisfied by the public. On the whole, this application can help the users to manage money and record income or expenses.